SYSTEMATIC LITERATURE REVIEW : "PENGARUH TEKNOLOGI MOBILE COMPUTING TERHADAP PENGALAMAN PENGGUNA DALAM TRANSAKSI MOBILE COMMERCE - AZ, Bambang; Veri, Jonh (Jurnal Ekonomi Bisnis Kompetif, 2025)
The development of mobile computing technology has revolutionized the way consumers interact with mobile commerce (m‑commerce) platforms, presenting both opportunities and challenges for service providers. This study aims to identify, analyze, and synthesize recent findings on the impact of mobile computing technology on user experience in m‑commerce transactions. A Systematic Literature Review (SLR) method was employed by searching the literature in leading databases such as Scopus, IEEE Xplore, and Google Scholar. The initial search yielded 200 articles relevant to the keywords. After a screening process based on inclusion and exclusion criteria, selected articles were analyzed in depth. The synthesis results indicate that factors such as access speed and connectivity stability, responsive and adaptive interface design, secure transactions, and the integration of wireless technologies (e.g., NFC and mobile wallets) have a significant influence on user satisfaction, trust, and loyalty. These findings affirm that the success of m‑commerce is determined not only by product or service quality but also by the technical performance and interaction experience provided. This study offers insights for developers, marketers, and researchers to design strategies for enhancing user experience based on advances in mobile computing.